2000
DOI: 10.1002/1522-2683(200011)21:17<3863::aid-elps3863>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The role of ATP, ADP and divalent cations in the formation of binary and ternary complexes of actin, cofilin and DNase I

Abstract: Actin is the major cytoskeletal protein of virtually all eukaryotic cells. Actin assembly/disassembly is involved in a variety of cellular processes and actin-binding proteins are essential in regulation of the pool of actin monomers. Cofilin and DNase I are actin-binding proteins, which form both binary (actin-DNase 1, cofilin-actin) and ternary (cofilin-actin-DNase I) complexes with actin. Here we use native gel electrophoresis to examine the roles of ATP, ADP, Ca2+ and Mg2+ in the formation of these complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…29 The existence of ternary complex demonstrates that the main interaction site of ADF or cofilin is the G-site. Binding does not occur at the F-site because DNase I binds monomeric actin very tightly and cannot be displaced by ADF or cofilin.…”
Section: Ternary Complexes Of Actin:dnase I and Cofilin Or Adfmentioning
confidence: 99%
“…29 The existence of ternary complex demonstrates that the main interaction site of ADF or cofilin is the G-site. Binding does not occur at the F-site because DNase I binds monomeric actin very tightly and cannot be displaced by ADF or cofilin.…”
Section: Ternary Complexes Of Actin:dnase I and Cofilin Or Adfmentioning
confidence: 99%
“…Formation of a cofilin-actinDNase I ternary complex has been demonstrated in vitro using both native (non-denaturing) PAGE gels [17] and Phast gels [18]. These reports determined that cofilin and DNase I bind cooperatively to actin forming a stable complex that is fairly insensitive to buffer conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated that the binding between cofilin, actin and DNase I in the ternary complex in vitro is essentially (Ca 2+ or Mg 2+ ) [17].Conversely, the cofilin-actin and actin-DNase I binary complexes are strongly influenced by buffer nucleotides and cations. The formation of the cofilin-actin-DNase I ternary complex has since been shown to be a cooperative process [18].…”
Section: Introductionmentioning
confidence: 87%
“…Dos Remedios and colleagues found the binary or ternary complexes among DNase I, actin and cofilin which suggested that DNase I could act as a stabilizer of actin monomers by effectively removing them from the pool of monomers available for the filament assembly. Thus DNase I could be a natural modulator on the action of cofilin in cytoskeleton [39,40].…”
Section: Cellular Functionsmentioning
confidence: 99%